Violence against women as a global scourge: Study of the countries visited between 2015 and 2020 by the Special Rapporteur of the United Nations on violence against women - Sanz Caballero, Susana (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2022)
The work makes a chronicle of the manifestations of violence against women detected by the Special Rapporteur on violence against women during her official visits between 2015-2020. The visits cover countries on the five continents and allow us to differentiate two large groups of cases: those of violence that are repeated in all the countries visited and those that are specific to the culture, religion and harmful traditions of a given geographic area. The types of violence that are repeated in all countries are domestic violence, sexual violence, trafficking in women and femicide. Among the particular cases are violence in divorce and inheritance proceedings in Israel, online harassment in the United Kingdom, zina in  Afghanistan, polygamy in Palestine, violence within gangs in Honduras, ablation in Sudan, etc. The articleindicates the need for a collective commitment, awareness, education and training work, social, political and economic change, as well as the need of collaboration of all the actors involved, starting with public authorities but continuing with civil society, companies, educational and health centres and families. The measures to be adopted should be of a legislative, administrative, social, educational, economic and political nature to be meaningful.
Keywords: Types of violence against women; United Nations; special rapporteur; generalized violence and specific violence